Sphingosine Kinase 1 Regulates Inflammation and Contributes to Acute Lung Injury in Pneumococcal Pneumonia via the Sphingosine-1-Phosphate Receptor 2. Issue 3 (March 2018) - Gutbier, Birgitt; Schönrock, Stefanie M.; Ehrler, Carolin; Haberberger, Rainer; Dietert, Kristina; Gruber, Achim D.; Kummer, Wolfgang; Michalick, Laura; Kuebler, Wolfgang M.; Hocke, Andreas C.; Szymanski, Kolja; Letsiou, Eleftheria; et al.
Abstract : Objectives: Severe pneumonia may evoke acute lung injury, and sphingosine-1-phosphate is involved in the regulation of vascular permeability and immune responses. However, the role of sphingosine-1-phosphate and the sphingosine-1-phosphate producing sphingosine kinase 1 in pneumonia remains elusive. We examined the role of the sphingosine-1-phosphate system in regulating pulmonary vascular barrier function in bacterial pneumonia. Design: Controlled, in vitro, ex vivo, and in vivo laboratory study. Subjects: Female wild-type and SphK1 -deficient mice, 8–10 weeks old. Human postmortem lung tissue, human blood–derived macrophages, and pulmonary microvascular endothelial cells. Interventions: Wild-type and SphK1 -deficient mice were infected with Streptococcus pneumoniae . Pulmonary sphingosine-1-phosphate levels, messenger RNA expression, and permeability as well as lung morphology were analyzed. Human blood–derived macrophages and human pulmonary microvascular endothelial cells were infected with S. pneumoniae . Transcellular electrical resistance of human pulmonary microvascular endothelial cell monolayers was examined. Further, permeability of murine isolated perfused lungs was determined following exposition to sphingosine-1-phosphate and pneumolysin. Measurements and Main Results: Following S. pneumoniae infection, murine pulmonary sphingosine-1-phosphate levels and sphingosine kinase 1 and sphingosine-1-phosphate receptor 2 expression were increased. Pneumonia-induced lung hyperpermeability was reduced in SphK1 –/– mice compared with wild-type mice. Expression of sphingosine kinase 1 in macrophages recruited to inflamed lung areas in pneumonia was observed in murine and human lungs. S. pneumoniae induced the sphingosine kinase 1/sphingosine-1-phosphate system in blood-derived macrophages and enhanced sphingosine-1-phosphate receptor 2 expression in human pulmonary microvascular endothelial cell in vitro. In isolated mouse lungs, pneumolysin-induced hyperpermeability was dose dependently and synergistically increased by sphingosine-1-phosphate. This sphingosine-1-phosphate–induced increase was reduced by inhibition of sphingosine-1-phosphate receptor 2 or its downstream effector Rho-kinase. Conclusions: Our data suggest that targeting the sphingosine kinase 1–/sphingosine-1-phosphate–/sphingosine-1-phosphate receptor 2–signaling pathway in the lung may provide a novel therapeutic perspective in pneumococcal pneumonia for prevention of acute lung injury. Abstract : Supplemental Digital Content is available in the text.